INTEGRASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBASIS STEM UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA PADA MATERI SPLTV DI KELAS X - Meilinda, Reza; Guntur, Guntur; Juliana, Nur; Hutahaean, Rispon (Jurnal Karya Pendidikan Matematika, 2024)
The STEM approach is an approach used to improve students' problem solving, critical and creative thinking abilities, and can be a foundation in preparing students for careers in technology, science and engineering. Therefore, researchers integrated a STEM-based Problem Based Learning model which aims to determine students' problem solving abilities in learning Mathematics on SPLTV material and prepare students to face the world of work. The subjects of this research were students of class X Nautika 2 at SMK Negeri 5 Tanjungpinang, Riau Islands, academic year 2023/2024. This type of research is Classroom Action Research (PTK) which is carried out in two cycles, namely cycle I and cycle II. The assessment instrument used is a test technique in the form of a description which is carried out at the end of each cycle. The data that has been collected from the test results is then analyzed descriptively to see the picture or percentage of actions that have been carried out. The results of the research show that the application of the STEM-based problem based learning model can increase problem solving abilities in the SPLTV material of class X Nautika 2 students at SMK Negeri 5 Tanjungpinang by 15%.